Wi-Fi security evaluation model based on BP neural network - Hai-yan KANG; Han YAN; Hao-ran HUANG; Xuan1 SUN (Tongxin xuebao)
A Wi-Fi security evaluation model was proposed based on BP neural network.Firstly a large number of Wi-Fi hotspots was analyzed,safety information sources about wireless hotspots were selected.Secondly,a model of BP neural network was constructed,the weights were adjusted,and the evaluation system for Wi-Fi safety was formed,which was higher credibility.Finally,on the Android flatform the application based on above theory was designed.A lot of experi-ments show the model is able to scan and evaluate the wireless hotspot around user.It can also provide the disconnect function on unsafe wireless hotspot.